Performance of the natural mortality factors of Aphis gossypii (Hemiptera: Aphididae) as a function of Cotton Plant variety and Phenology - Chamuene, António; Araújo, Tamíris Alves; Silva, Gerson; Costa, Thiago Leandro; Berger, Paulo Geraldo; Picanço, Marcelo Coutinho (Environmental Entomology, 2017)
Natural mortality factors are responsible for regulating pest populations in the field. However, plant attributes such as the variety and phenological stage can influence the performance of these factors. Therefore, we investigated the performance of the natural mortality factors of Aphis gossypii (Glover; Hemiptera: Aphididae) as a function of the plant variety and phenology. To investigate the performance of these factors, we evaluated the mortality of A. gossypii caused by natural mortality factors for 2 yr in field conditions in transgenic (Bacillus thuringiensis/Roundup Ready) and non-transgenic cotton crops during vegetative, flowering, and fruiting stages. The natural mortality factors were affected similarly between the transgenic and non-transgenic plants; however, differences were observed in their performance, depending on the phenological stage of the cotton plant. Compared with other stages, predation was higher in the flowering stage, whereas the mortality caused by rainfall was higher in the vegetative stage. Coccinellid beetles were primarily responsible for the predation on A. gossypii. These findings highlight that the performance of the natural mortality factors of A. gossypii varied more as a function of the phenological stage of cotton than of the variety.
Keywords: Cotton aphid; Natural enemies; Physiological disorder; Rainfall